Validation of the state impulsivity scale in students from a university in Lima, Peru - Silva-Dominguez, Daniel (2025)
Objective: To analyze the psychometric properties and validate the State Impulsivity Scale (SIS) in university students from Lima, Peru. Methods: This was a psychometric, descriptive, and cross-sectional study. The sample consisted of 954 students (361 women and 593 men), who were evaluated with the SIS by Iribarren et al. (18). A parallel analysis was conducted across three dimensions, along with an exploratory factor analysis. Additionally, several ft indices were used for a more comprehensive evaluation and analysis. Results: The results indicate that the three-factor model proposed by the authors presented the best ft indices (CFI = 0.973, TLI = 0.964, SRMR = 0.039, and RMSEA = 0.049), showing evidence of construct validity. Likewise, adequate reliability values were shown (gratifcation, F1, a = 0.833 and w = 0.790; automatism, F2, a = 0.854 and w = 0.810; attentional, F3, a = 0.874 and w = 0.835; and total scale a = 0.936 and w = 0.917). Finally, no evidence of invariance was found according to sex (CFI > 0.001). Conclusions: The State Impulsivity Scale provides psychometric evidence for its use.